Early MRI predictors of disease‐free survival in locally advanced rectal cancer from the GRECCAR 4 trial. Issue 11 (22nd August 2019) - Nougaret, S.; Castan, F.; de Forges, H.; Vargas, H. A.; Gallix, B.; Gourgou, S.; Rouanet, P.
Abstract : Background: Tailored neoadjuvant treatment of locally advanced rectal cancer (LARC) may improve outcomes. The aim of this study was to determine early MRI prognostic parameters with which to stratify neoadjuvant treatment in patients with LARC. Methods: All patients from a prospective, phase II, multicentre randomized study (GRECCAR4; NCT01333709) were included, and underwent rectal MRI before treatment, 4 weeks after induction chemotherapy and after completion of chemoradiotherapy (CRT). Tumour volumetry, MRI tumour regression grade (mrTRG), T and N categories, circumferential resection margin (CRM) status and extramural vascular invasion identified by MRI (mrEMVI) were evaluated. Results: A total of 133 randomized patients were analysed. Median follow‐up was 41·4 (95 per cent c.i. 36·6 to 45·2) months. Thirty‐one patients (23·3 per cent) developed tumour recurrence. In univariable analysis, mrEMVI at baseline was the only prognostic factor associated with poorer outcome ( P = 0·015). After induction chemotherapy, a larger tumour volume on MRI ( P = 0·019), tumour volume regression of 60 per cent or less ( P = 0·002), involvement of the CRM ( P = 0·037), mrEMVI ( P = 0·026) and a poor mrTRG ( P = 0·023) were associated with poor outcome. After completion of CRT, the absence of complete response on MRI ( P = 0·004), mrEMVI ( P = 0·038) and a poor mrTRG ( P = 0·005) were associated with shorter disease‐free survival. A final multivariable model including all significant variables (baseline, after induction, after CRT) revealed that Eastern Cooperative Oncology Group performance status ( P = 0·011), sphincter involvement ( P = 0·009), mrEMVI at baseline ( P = 0·002) and early tumour volume regression of 60 per cent or less after induction ( P = 0·007) were associated with relapse. Conclusion: Baseline and early post‐treatment MRI parameters are associated with prognosis in LARC. Future preoperative treatment should stratify treatment according to baseline mrEMVI status and early tumour volume regression. Abstract : Patients with locally advanced rectal cancer from the multicentre phase II randomized study GRECCAR 4 were included in the study, and underwent rectal MRI before and after induction chemoradiotherapy. Baseline and early post‐treatment MRI parameters were associated with prognosis in locally advanced rectal cancer. Future preoperative therapy evaluation will need to stratify treatment according to baseline extramural vascular invasion status and early tumour volume regression. Tailored treatment possible Abstract : Antecedentes: El tratamiento neoadyuvante personalizado del cáncer de recto localmente avanzado ( locally advanced rectal cancer, LARC) puede mejorar los resultados. El objetivo de este estudio fue determinar factores pronósticos precoces mediante RMN para estratificar el tratamiento neoadyuvante en pacientes con LARC. Métodos: Todos los pacientes de un eensayo prospectivo de fase II, multicéntrico y aleatorizado (GRECCAR4‐NCT01333709) se incluyeron en este estudio y se les realizó una RMN antes del tratamiento, 4 semanas después de la quimioterapia de inducción y después de completar la quimiorradioterapia ( chemoradiation, CRT). Se evaluó la volumetría tumoral, el grado de regresión tumoral mediante RMN ( MRI Tumor Regression Grade, mrTRG), la estadificación T, la estadificación N, el estado del margen de resección circunferencial ( circumferential resection margin, CRM) y la presencia de invasión extramural vascular en la RMN ( extramural vascular invasion, mrEMVI). Resultados: Se analizaron 133 pacientes aleatorizados. La mediana de seguimiento fue de 41, 4 meses (i.c. del 95%: 36, 6‐45, 2). En 31 pacientes (23%) se diagnosticó una recidiva. En el análisis univariado de la situación basal, mrEMVI fue el único factor pronóstico asociado con un peor resultado ( P = 0, 0152). Después de la quimioterapia de inducción, un volumen tumoral más alto en la RMN ( P = 0, 019), una regresión del volumen tumoral ≤ 60% ( P = 0, 002), la afectación del CRM ( P = 0, 037), mrEMVI ( P = 0, 026) y un grado escaso mrTRG ( P = 0, 023) se asociaron con un mal resultado. Después de completar la CRT, la ausencia de respuesta completa en la RMN ( P = 0, 004), la presencia de mrEMVI ( P = 0, 04) y una insuficiente mrTRG ( P = 0, 005) se asociaron con una supervivencia libre de enfermedad más corta. En el modelo multivariable final en el que se incluyeron todas las variables significativas (basales, postinducción, post‐CRT), el estado de ECOG ( P = 0, 011), la afectación esfinteriana ( P = 0, 009), la presencia de EMVI al inicio ( P = 0, 002) y una regresión precoz del volumen tumoral ≤ 60% después de la inducción ( P = 0, 007) se asociaron con una recidiva. Conclusión: Los parámetros basales y post‐tratamiento precoces de la RMN se asocian con el pronóstico en el LARC. La estrategia terapéutica preoperatoria futura deberá estratificar el tratamiento de acuerdo con la presencia de EMVI al inicio y la regresión precoz del volumen tumoral.